Satisfaction Level among Patients Treated with Fixed Dental Prosthesis in a Tertiary Care Hospital: A Descriptive Cross-sectional Study - Shrestha, Lajana (JNMA J Nepal Med Assoc, 2020)
INTRODUCTION: Dental treatment aims at correction of existing disease; prevention of future disease with rehabilitation of patient's lost functional capacity and aesthetics. Fixed dental prosthesis is any prosthesis that is cemented to a natural tooth or dental implants abutments that cannot be removed by patient. The success of prosthodontic treatment is related to prosthesis survival, with its ability to fulfil biologic and patient-evaluated objectives with patient satisfaction. This study is aimed to find the patient satisfaction with fixed prosthodontic treatment. METHODS: This descriptive cross-sectional study was done in a tertiary care hospital among 102 patients rehabilitated with fixed dental prosthesis from August to September 2019 after taking ethical approval from Institutional Review Committee of Kathmandu Medical College. (IRC No. 1207201918). Convenience sampling was done. The questionnaire assessed patient's satisfaction of fixed prosthesis on the basis of appearance, chewing ability, cleansibility, speech and awareness of oral hygiene measures for cleaning of the prosthesis. Data entry was done in Microsoft excel and analysed using Statistical Package for Social Sciences (SPSS)version 20.0, point estimate at 95% Confidence Interval was calculated along with frequency and proportion for binary data. RESULTS: The majority of the patients 87 (85.3%) were satisfied with their fixed prosthesis, at 95% confidence interval (93.5-81%). Eighty one (79.4%) were satisfied with their chewing ability; 99 (97.1%) satisfied with their speech, 78 (76.4%) satisfied with appearance of fixed prosthesis. Ninety eight patients (96.1%) were aware of oral hygiene measures, out of which only 66 (67.3%) used interdental aids for cleaning of their fixed prosthesis. CONCLUSIONS: Several factors (chewing ability, appearance, speech, cleansibility of fixed prosthesis) had positive impact on overall satisfaction in majority of the patients. Dentists should continue to emphasise on the significance of maintaining good oral hygiene and use of interdental aids for the longevity of fixed prosthesis.